STRATEGI GREEN HUMAN RESOURCE PADA PERUSAHAAN MANUFAKTUR - Fitry, Emli; Nurhakim, Warsudi; Aziz, Apud Abdul (Jurnal Ekonomi dan Bisnis (EK&BI), 2025)
The manufacturing industry plays a vital role in the global economy but also significantly contributes to the depletion of natural resources and environmental pollution. Therefore, implementing Green Human Resource Management (GHRM) is a crucial strategy to ensure sustainable operations while preserving the environment. This study aims to identify key strategies for implementing GHRM in the manufacturing industry, including eco-friendly recruitment, environmentally focused training and development, green performance evaluation, and employee involvement in sustainable innovation. Through this approach, companies can integrate sustainability principles into their human resource management systems, enhancing energy efficiency, reducing waste, and complying with environmental standards such as ISO 14001. The findings indicate that adopting GHRM in the manufacturing industry positively impacts the environment and provides business advantages, including improved operational efficiency, competitive advantage, and regulatory compliance. Additionally, employee engagement in green innovation is proven to be a key factor in fostering a sustainability-oriented workplace culture. Therefore, GHRM should serve as a primary reference in formulating human resource policies in the manufacturing sector to create a more environmentally friendly, innovative, and sustainable production system